Self-Confidence of The Rugby Athletes of The Responsible Contingent Following The PON XXI Championship Aceh-Sumut 2024 - Ayyash, Fairuz Muhammad; Dinangsit, Dinar; Rahman, Aam Ali (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to evaluate the self-confidence level of rugby athletes from the West Java contingent participating in the 2024 National Sports Week (PON XXI) in Aceh, North Sumatra, and to identify the influencing factors. Self-confidence is a crucial psychological aspect that affects an athlete’s performance, especially under the pressure of national-level competition. This research employed a qualitative approach with a case study design, involving four athletes as participants. Data were collected through questionnaires and in-depth interviews and analyzed using thematic techniques. The findings revealed variations in self-confidence levels, with two athletes categorized as moderate and the other two as high. Internal factors such as competitive experience, physical readiness, and self-concept, along with external factors including social support and educational background, were found to shape the athletes’ self-confidence. These results provide important insights for designing more effective mental training strategies to support athletes in preparing for high-level sports competitions.